Introduction: The Ambiguities of Risk in the Early Republic - Matson, Cathy (Business History Review, 2004)
In the half-century following the American Revolution, journalists and promoters of economic activities wrote paeans to the independence movement, celebrating its release of economic energies and anticipating that it would enable citizens to improve, produce, and consume more and thus sustain their virtuous republican character as a people. Writers predicted that imminent prosperity would result in the construction of mills, forges, and retail networks throughout the hinterlands; they envisioned boldly experimental internal improvements and expanding commerce under the independent auspices of the newly formed states and locales. Liberated Americans could look forward to blending certain kinds of regulatory protections and government encouragements, such as they had experienced under the rule of the empire, and to the aggressive pursuit of economic opportunities: creating new kinds of taxation and currency systems, expanding commerce to foreign ports, extending agriculture to the limits of available technologies and capital, and testing modest manufactures. For two generations following the Revolution, until at least the panic of 1819, many optimists were confirmed in their expectations of a bright future for the new nation's economy, and they embraced the risks involved in mobilizing tremendous amounts of human energy and capital because they believed that economic development would resolve foreign nations' doubts about the new republic and obliterate the crushing debts and dislocations of the revolutionary war.
Keywords: Business History and gender